Face-to-face vs. online peer support groups for prostate cancer: A cross-sectional comparison study - Huber, Johannes; Muck-Böhme, Tanja; Maatz, Philipp; Keck, Bastian; Enders, Paul; Maatouk, Imad; Ihrig, Andreas (Journal of cancer survivorship, 2018)
BackgroundAs social media are evolving rapidly online support groups (OSG) are becoming increasingly important for patients. Therefore, the aim of our study was to compare the users of traditional face-to-face support groups and OSG.Patients and methodsWe performed a cross-sectional comparison study of all regional face-to-face support groups and the largest OSG in Germany. By applying validated instruments, the survey covered sociodemographic and disease-related information, decision-making habits, psychological aspects, and quality of life.ResultsWe analyzed the complete data of 955 patients visiting face-to-face support groups and 686 patients using OSG. Patients using OSG were 6 years younger (65.3 vs. 71.5 years; p < 0.001), had higher education levels (47 vs. 21%; p < 0.001), and had higher income. Patients using OSG reported a higher share of metastatic disease (17 vs. 12%; p < 0.001). Patients using OSG reported greater distress. There were no significant differences in anxiety, depression, and global quality of life. In the face-to-face support groups, patient ratings were better for exchanging information, gaining recognition, and caring for others. Patients using OSG demanded a more active role in the treatment decision-making process (58 vs. 33%; p < 0.001) and changed their initial treatment decision more frequently (29 vs. 25%; p < 0.001).ConclusionsBoth modalities of peer support received very positive ratings by their users and have significant impact on treatment decision-making.Implications for cancer survivorsOlder patients might benefit more from the continuous social support in face-to-face support groups. OSG offer low-threshold advice for acute problems to younger and better educated patients with high distress.Trial registration www.germanctr.de, number DRKS00005086